The Potential of Bison Restoration as an Ecological Approach to Future Tribal Food Sovereignty on the Northern Great Plains - Shamon, Hila; Cosby, Olivia G.; Andersen, Chamois L.; Augare, Helen; BearCub Stiffarm, Jonny; Bresnan, Claire E.; Brock, Brent L.; Carlson, Ervin; Deichmann, Jessica L.; Epps, Aaron; Guernsey, Noelle; Hartway, Cynthia; et al. (Frontiers in Ecology and Evolution, 2022)
Future climate projections of warming, drying, and increased weather variability indicate that conventional agricultural and production practices within the Northern Great Plains (NGP) will become less sustainable, both ecologically and economically. As a result, the livelihoods of people that rely on these lands will be adversely impacted. This is especially true for Native American communities, who were relegated to reservations where the land is often vast but marginal and non-tribal operators have an outsized role in food production. In addition, NGP lands are expected to warm and dry disproportionately relative to the rest of the United States. It is therefore critical to identify models of sustainable land management that can improve ecological function and socio-economic outcomes for NGP communities, all while increasing resilience to a rapidly changing climate. Efforts led by Native American nations to restore North American Plains bison (Bison bison bison) to tribal lands can bring desired socio-ecological benefits to underserved communities while improving their capacity to influence the health of their lands, their people, and their livelihoods. Ecological sustainability will depend on the restoration of bison herds and bison’s ability to serve as ecosystem engineers of North America’s Plains. The historically broad distribution of bison suggests they can adapt to a variety of conditions, making them resilient to a wide range of management systems and climates. Here we review bison's ecological, cultural, and economic value using four case studies from tribal communities within the NGP. We discuss the potential contributions of bison to food sovereignty, sustainable economies,